Mathematical Connection Ability through the Application of the AIR (Auditory Intellectualy Repetition) Learning Model Assisted by Geogebra Software - Ainal Mardhiah; M. Ikhsan; Muhammad Subianto (International Journal of Education and Digital Learning (IJEDL), 2023)
expected model scan fosters students' mathematical connection skills, namely through the application of the AIR (Auditory Intellectual Repetition) model assisted by geogebra software. The purpose of this study was to determine differences in students' mathematical connection abilities after obtaining learning by applying the AIR (Auditory Intellectual Repetition) model assisted by geogebra software. This study used a quantitative approach with a pre-test and post-test control group design. The population of this study was class IX students of SMPN 1 Peukan Pidie by taking samples of two classes consisting of an experimental class and a control class. The sample selection was done by random sampling. The instrument used is a mathematical connection ability test. The data analysis technique uses the ANOVA test. Based on the results of the study, it was found that there were differences in the mathematical connection abilities of students who were taught through the application of the AIR (Auditory Intellectual Repetition) model assisted by geogebra software with conventional learning. Furthermore, the results of this study also identified that there was no interaction between learning and student level on students' mathematical connection abilities.